1973
DOI: 10.1139/z73-122
|View full text |Cite
|
Sign up to set email alerts
|

Lungworms in the Rocky Mountain bighorn sheep of western Canada

Abstract: In 58 sets of lungs from bighorns from western Alberta or eastern British Columbia, 91% were infected with Protostrongylus stilesi, and 38% were infected with P. rushi. Four of the five sheep free of P. stilesi were lambs. Lungs from nine near-term fetuses were negative for lungworms.All but 1 of 409 field-collected fecal samples from the same ranges contained larvae of Protostrongylus spp.; counts of larvae per gram of dry feces suggest a clumped distribution of lungworms. Analysis of monthly samples from one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Median larvae counts are based on fecal samples collected May through August in each year. Although larval output in bighorn feces differs significantly between late winter/early spring and summer/fall (Uhazy et al, 1973;Goldstein et al, 2005), variation in fecal larvae counts between May and October was not significant (Uhazy et al, 1973). However, reported seasonal patterns differ among populations (Arnett et al, 1993); therefore, we tested for variation in fecal larvae counts among months (May-August) in each year.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Median larvae counts are based on fecal samples collected May through August in each year. Although larval output in bighorn feces differs significantly between late winter/early spring and summer/fall (Uhazy et al, 1973;Goldstein et al, 2005), variation in fecal larvae counts between May and October was not significant (Uhazy et al, 1973). However, reported seasonal patterns differ among populations (Arnett et al, 1993); therefore, we tested for variation in fecal larvae counts among months (May-August) in each year.…”
Section: Discussionmentioning
confidence: 97%
“…Lungworm larval output in bighorn sheep feces may be related to infection intensity (Forrester and Senger, 1964;Uhazy et al, 1973), but is also likely to be influenced by a variety of other factors, such as the immune response of the host or density-dependence of parasite fecundity (Festa-Bianchet, 1991a;Wilson et al, 2002). Although sensitivity of indirect measures to detect prevalence may be low (Wilson et al, 2002), repeated sampling of known bighorn sheep revealed few false-negatives using fecal counts of lungworm larvae (Festa-Bianchet, 1991a).…”
Section: Bighorn Sheep Distribution and Fecal Analysismentioning
confidence: 99%
“…Cyclical seasonal patterns of LPG occur in many bighorn sheep herds, but patterns vary geographically even in similar temperate zones (Uhazy et al, 1973;Arnett et al, 1993). Some studies have correlated precipitation and adult lungworm loads (Forrester and Littell, 1976), but others failed to demonstrate a relationship between precipitation and fecal larval load (Festa-Bianchet, 1991;Goldstein, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary compromise caused by Protostrongylus spp. in bighorn sheep has been implicated as a predisposing factor in bacterial and viral pneumonia outbreaks (Forrester 1971;Uhazy et al 1972;Spraker et al 1984), and infection with these parasites may decrease alveolar macrophage viability in vitro (Silflow and Foreyt 1988). Umingmakstrongylus pallikuukensis differs from these lungworms in that, in established infections, pathology seems to be localized to the cysts, leaving most of the lung tissue in adult muskoxen unaffected.…”
Section: Host-parasite Biologymentioning
confidence: 99%